Impact of fiscal policy in an intertemporal CGE model for South Africa - (:unkn) unknown (My University, 2013)
JEL classification: D58 D92 H54 H59 Keywords: Intertemporal CGE model New growth path Infrastructure Total factor productivity South Africa This paper uses an intertemporal computable general equilibrium model to investigate the consequences of an expansive fiscal policy designed to accelerate economic growth in South Africa. A key contribution is made to existing literature on the transmission mechanism of fiscal policy in African economies. To the best of our knowledge , no published study has empirically analyzed the macroeconomic effects of fiscal policy in the context of an open, middle-income sub-Saharan African economy like South Africa using an integrated intertemporal model with such disaggregated production structure. The paper shows that an expansive fiscal policy would have a temporary impact on gross domestic product (GDP) but would translate into higher debt relative to GDP. Using increased taxation to finance the additional spending would lessen this impact but would also negatively affect macroeconomic variables. Increased investment spending would improve long-term GDP, under any financing scheme, and would decrease debt-to-GDP ratio as well as deficit-to-GDP ratio. This outcome is driven by the positive impact infrastructure has on total factor productivity. Sensitivity analysis shows that these conclusions are qualitatively similar for wide values of the elasticity of the total factor productivity to infrastructure. In fact, the conclusions hold even when comparing different financing schemes.
Keywords: African Research